HUBUNGAN PENGETAHUAN SISWA SEKOLAH DASAR DENGAN KONSUMSI MINUMAN SERBUK INSTAN DI SD NEGERI SENDANG MULYO 03 SEMARANG - Elisa Henny; Apoina Kartini; M. Zen Rahfiludin (Jurnal Kesehatan Masyarakat (Undip), 2015)
Artificial sweetners are food additives which can cause a sweet taste in food, but it has no nutritional value. The artificial sweetners which are used exceeds the normal limits can affect for health, but in the fact artificial sweetners is used to reduce the cost of production and children at the school age are the most consument of instant drink in powder form. This research is purpose to determine correlation of elementary school students’ knowledge and frequency consumption of instant drink in powder form. The types of research is used sectional cross design. The respondents for this research are elementary school students at three, four, and five grade as many as 81 people were take by simple random sampling. Bivariate analysis used Rank Spearman test. The result showed some knowledge of instant drink is good (72,6%) and frequency consumption are often (74,1%). Laboratory results of the three types of instant powder drrinks were tested (guava of Marimas, sweet mango of NutriSari, and Milo) showed guava of Marimas and sweet mango of NutriSari are positive containing saccharin(976,46 ppm) and (911,62 ppm), but Milo is not containing of saccharin. Stastistical test showed there was no correlation of elementary school students knowledge and frequency consumption of instant drink in powder from (p=0,473). Suggested from this result research that had good knowledge needs to be balanced by good manners as well in order to reduce the number of frequency of consumption of instant drink in powder form.